Bow-Wow bugs a bug - Newgarden, Mark.; Cash, Megan Montague (Orlando : Harcourt, 2007)
A wordless picture book about a persistent terrier who follows a bug through his neighborhood.
A Junior Library Guild selection
Keywords: Terriers -- Fiction; Dogs -- Fiction; Insects -- Fiction; Stories without words; Terriers -- Juvenile fiction; Dogs -- Juvenile fiction; Insects -- Juvenile fiction